2021
DOI: 10.1038/s41398-021-01528-y
|View full text |Cite
|
Sign up to set email alerts
|

Conserved immunomodulatory transcriptional networks underlie antipsychotic-induced weight gain

Abstract: Although antipsychotics, such as olanzapine, are effective in the management of psychiatric conditions, some patients experience excessive antipsychotic-induced weight gain (AIWG). To illuminate pathways underlying AIWG, we compared baseline blood gene expression profiles in two cohorts of mice that were either prone (AIWG-P) or resistant (AIWG-R) to weight gain in response to olanzapine treatment for two weeks. We found that transcripts elevated in AIWG-P mice relative to AIWG-R are enriched for high-confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Our recent study identified that inflammation potentiates AP-induced hyperphagia and weight gain 33 . Since inflammation is regulated in part by the circadian clock 34 , we evaluated whether the timing of AP dosing affects inflammation in metabolically active tissues (hypothalamus, liver and gWAT).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our recent study identified that inflammation potentiates AP-induced hyperphagia and weight gain 33 . Since inflammation is regulated in part by the circadian clock 34 , we evaluated whether the timing of AP dosing affects inflammation in metabolically active tissues (hypothalamus, liver and gWAT).…”
Section: Resultsmentioning
confidence: 98%
“…Vehicle control pellets were then given to unfasted mice for an additional 3 consecutive days to overcome any novelty-associated behavior changes in feeding and locomotion. After training, mice consumed the pellet in less than ~15 min 33 allowing for precisely timed AP dosing. Dosing time was ~2 h after lights on between 8:00–8.30AM, (Zeitgeber time (ZT) 2) for the ‘AM’ group and between 5:30–6:00PM, ZT 11 for the ‘PM’ group.…”
Section: Methodsmentioning
confidence: 99%
“…1B ) compared to vehicle treatment. While in general AP-drugs drive hyperphagia and weight gain, there is significant variation in the magnitude of these effects 79 . In our recent study, 29 we measured antipsychotic-induced weight gain (AIWG) in mice and stratified into subgroups that were highly prone to weight gain (gained 6.3g body weight) and weight gain resistant (gained 1.3g body weight) 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Our recent study identified that inflammation potentiates AP-induced hyperphagia and weight gain (20). Since inflammation is regulated in part by the circadian clock (21), we evaluated whether the timing of AP dosing affects inflammation in metabolically active tissues (hypothalamus, liver and gWAT).…”
Section: Resultsmentioning
confidence: 99%
“…Placebo control pellets were then given to unfasted mice for an additional 3 consecutive days to overcome any novelty-associated behavior changes in feeding and locomotion. After training, mice consumed the pellet in less than ∼15 mins (20) allowing for precisely timed AP dosing. Dosing time was approximately 2 h after lights on between 8:00-8.30AM, (Zeitgeber time (ZT) 2) for the ‘AM’ group and between 5:30-6:00PM, ZT 11 for the ‘PM’ group.…”
Section: Methodsmentioning
confidence: 99%